Gender Discrimination and Nursing: A Literature Review - Kaite, Charis P.; Kouta, Christiana (My University, 2011)
This article aims to examine gender stereotypes in relation to men in nursing, discuss gender discrimination cases in nursing, and explore methods used for promoting equal educational opportunities during nursing studies. The literature review was based on related databases, such as CINAHL, Science Direct, MEDLINE, and EBSCO. Legal case studies are included in order to provide a more practical example of those barriers existing for men pursuing nursing, as well as statistical data concerning gender discrimination and male attrition to nursing schools in relation to those barriers. These strengthen the validity of the manuscript. Literature review showed that gender discrimination is still prevalent within nursing profession. Nursing faculty should prepare male nursing students to interact effectively with female clients as well. Role modeling the therapeutic relationship with clients is one strategy that may help male students. In general, the faculty should provide equal learning opportunities to nursing students.
Keywords: Educational strategies; Gender roles; Gender stereotypes; Male nurses; Nursing